Case report: EGFR-TKI rechallenge after osimertinib-induced interstitial lung disease: a case report and literature review - Gu, Xiaofei; Zhong, Yonghong; Huang, Huaqiong (Frontiers in Pharmacology, 2024)
Background Osimertinib, a third-generation tyrosine kinase inhibitor (TKI), has demonstrated significant efficacy in treating non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations. However, EGFR-TKI-induced interstitial lung disease (ILD), a well-known adverse effect, can seriously affect the treatment outcome. There is currently no international consensus on the efficacy and safety of re-administration of EGFR-TKI after EGFR-TKI-induced ILD. Case summary We report a case of a 62-year-old male with stage IV lung adenocarcinoma and EGFR L858R mutation who was treated with osimertinib at a dose of 80 mg/day as first-line therapy. On the sixth day of treatment, the patient developed grade 4 ILD, chest tightness, shortness of breath, and paroxysmal dry cough. Arterial blood gas analysis indicated the presence of type I respiratory failure, while the chest CT scan revealed newly developed ground-glass opacities in both lungs and a considerable amount of pleural effusion on the left side. Subsequently, the patient was administered methylprednisolone for anti-inflammatory therapy, in conjunction with oxygen therapy, anti-infection treatment, and closed thoracic drainage, which resulted in a favourable recovery and discharge after 18 days. During this period, the patient adhered to third-generation EGFR-TKI oral targeted therapy. Nevertheless, within a week of discharge, the patient was readmitted due to the recurrence of chest tightness and shortness of breath. A chest CT scan indicated a recurrent ILD. Despite the administration of high-dose methylprednisolone for 9 days, the patient’s condition continued to deteriorate, ultimately resulting in death. Conclusion It is of the utmost importance to conduct a meticulous evaluation of the severity of osimertinib-induced ILD in order to ascertain the potential risks and benefits of EGFR-TKI rechallenge. Particularly, for patients with grade 4 ILD, firm drug discontinuation should be considered.